Performansi Teknologi 10 – Gigabit Passive Optical Network (XGPON) Pada Jaringan Fiber to the Home (FttH) Dd Daerah Sub – Urban - Raihan, Mochamad Alif; Nur, Levy Olivia; Novfitri, Aisyah (eProceedings of Engineering, 2024)
Current technological advancements, particularly in information and communication technology, are rapidly evolving. The demand for information and communication technology services has expanded beyond voice services to include data, images, and video. Fiber optic cables are now widely used in technology and communications due to their ability to transmit large amounts of information at high speeds. The technology of using fiber optic cables as a transmission medium in telecommunication systems is known as Fiber Optic Local Area Network (FOTLN). One development of FOTLN is Fiber to the Home (FTTH). This final project conducts a study on